PENGEMBANGAN KARAKTER MAHASISWA DALAM BIDANG KEWIRAUSAHAAN MELALUI IMPLEMENTASI MEMBANGUN BISNIS KULINER STUDI KASUS: BAKMI BANDUNG DI PEMALANG - Jumhuriyatus Sa’diyah; Farah Dilah Zahra; Muhammad Nur Ilham; M. Iqodzul Himam Abil Izz; Ferida Rahmawati (CV. Denasya Smart Publisher, 2025)
The world of higher education needs graduates who are not only well educated but also have strong character and are ready to compete. Entrepreneurship is seen as one of the best ways to build character values. Direct implementation through business creation, especially in the culinary industry which has a wide market, gives students real experiences. This case study was conducted on a Bakmi Bandung business in Pemalang using observation and interview methods. The results show that the process of building a business effectively develops key entrepreneurial characteristics such as independence, creativity, perseverance, responsibility, and management skills. The study concludes that real business implementation is a contextual and effective learning method to build character and entrepreneurial mindset in students.